2007
DOI: 10.1089/gte.2006.9994
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Frequencies of The 35delG Mutation of The GJB2 Gene in Different Brazilian Regions

Abstract: Mutations in the GJB2 gene, which encodes the protein connexin 26, are a major cause of autosomal recessive deafness. The most frequent mutation, 35delG, has a carrier frequency as high as 4% in some countries, and this frequency varies in different ethnic groups. Most of the Brazilian population results from interethnic crosses of people from three continents (European, African, and Amerindian), and the proportion of each varies according to the geographical region of the country. To verify if the different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
1
7
0
7
Order By: Relevance
“…In spite of the difference in sample selection criteria, the frequency of individuals presenting c.35delG mutation in the GJB2 gene (12.4%) in our study was similar to that found (13.9%) in the report of de Oliveira et al (2007). Our study agrees with these previous reports (de Oliveira, et al, 2007;Oliveira, et al, 2002;Piatto, et al, 2004), showing that the c.35delG mutation is the most frequent among causative mutations of hearing impairment in the Brazilian population. This is a common mutation causing HL in Caucasian populations, mainly from Mediterranean Europe and the United States, and seems to be rare in the Asian and African populations.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of the difference in sample selection criteria, the frequency of individuals presenting c.35delG mutation in the GJB2 gene (12.4%) in our study was similar to that found (13.9%) in the report of de Oliveira et al (2007). Our study agrees with these previous reports (de Oliveira, et al, 2007;Oliveira, et al, 2002;Piatto, et al, 2004), showing that the c.35delG mutation is the most frequent among causative mutations of hearing impairment in the Brazilian population. This is a common mutation causing HL in Caucasian populations, mainly from Mediterranean Europe and the United States, and seems to be rare in the Asian and African populations.…”
Section: Discussionsupporting
confidence: 91%
“…Jaqueline Medeiros de Mello (1) , Ana Maria Silveira Machado de Moraes (2) , Jeferson Cedaro de Mendonça (3) , Daniela Álvares da Silva (4) , Laise Adriane Hegeto (5) , Valter Augusto Della-Rosa (6) RESUMO Objetivo: verificar a prevalência da deficiência auditiva em um programa de triagem auditiva neonatal e investigar mutações do gene GJB2 naqueles com suspeita de deficiência auditiva. Método: foi realizado estudo longitudinal com 908 RN a termo, pós-termo e pré-termo que foram submetidos à realização da triagem auditiva por meio do teste de Emissão Otoacústica Evocada por Estímulo Transiente (EOA-T) e reflexo cócleo-palpebral (RCP).…”
Section: Newborn Hearing Screening: From Audiological Alterations To unclassified
“…(5) Acadêmica do 5º ano do Curso de Ciências Biológicas da Universidade Estadual de Maringá -UEM, Maringá,PR. (6) Biomédico; Docente na área de Genética da Universidade Estadual de Maringá -UEM, Maringá, PR; Doutor em Ciências Biológicas e Genética pela Universidade de São Paulo -USP.…”
Section: Descritoresunclassified
See 2 more Smart Citations